2003
DOI: 10.1007/s11664-003-0109-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooling rate on the microstructure and tensile behavior of a Sn-3.5wt.%Ag solder

Abstract: The tensile behavior and microstructure of bulk, Sn-3.5Ag solders as a function of cooling rate were studied. Cooling rate is an important processing parameter that affects the microstructure of the solder and, therefore, significantly influences mechanical behavior. Controlled cooling rates were obtained by cooling specimens in different media: water, air, and furnace. Cooling rate significantly affected secondary dendrite-arm size and spacing of the Sn-rich phase, as well as the aspect ratio of Ag 3 Sn. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(99 citation statements)
references
References 18 publications
5
94
0
Order By: Relevance
“…It is known that the bismuth additions can significantly depressed the melting temperature of Sn-Ag-based lead-free solder alloys [13,14]. Further advantage of adding bismuth into Sn-Ag system solder is the improvement of solder wetting/spreading behaviour [15,16]. It was also already shown that bismuth and silver can have a significant impact on the corrosion properties in case of Sn-based solder alloy in NaCl solutions [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the bismuth additions can significantly depressed the melting temperature of Sn-Ag-based lead-free solder alloys [13,14]. Further advantage of adding bismuth into Sn-Ag system solder is the improvement of solder wetting/spreading behaviour [15,16]. It was also already shown that bismuth and silver can have a significant impact on the corrosion properties in case of Sn-based solder alloy in NaCl solutions [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a number of studies on mechanical fatigue of solder alloys to understand fatigue failure of solder joints have been performed to date. In general, mechanical properties of solder alloys such as creep and fatigue are measured using larger volume bulk specimens than real solder joints [1][2][3][4][5] as there are many difficulties in sample preparation and mechanical testing. However, the microstructure of the real joint is totally different to that of the large size mechanical testing specimen, since solidification conditions of real joints cannot be duplicated in large size.…”
Section: Introductionmentioning
confidence: 99%
“…For Sn-3.5Ag/Cu couples at 170 °C and at 205 °C a t 0.42 time dependence has been found for the Cu 3 Sn growth [15]. The kinetics for the intermetallic formation and the intermetallic microstructure depend for instance on the cooling rate [16] and the presence of other elements in the coating bath, such as Cu [17], which is dissolved in the coating bath from the strand during the coating process.…”
Section: Introductionmentioning
confidence: 93%